J09 A new trial design for evaluating exercise outcomes in huntington's disease. (September 2018) - Busse, Monica; Quinn, Lori; Drew, Cheney; Williams-Thomas, Rhys; Dimitropoulou, Polyxeni; Playle, Rebecca; Hamana, Katy; Griffin, Beth Ann; Reilmann, Ralf; Kelson, Mark; Rosser, Anne
Abstract : Background and aims: Across the Huntington's Disease (HD) communities, there has been some success in delivering exercise interventions in HD over the short term. In order to move the field forward we now need studies with longer term follow-up to elucidate the potential effect of exercise and physical activity on disease progression. The efficient use of existing data and consideration of patient preferences is critical for evaluation of non-drug interventions where recruitment and retention are challenging. Methods: In PACE-HD we utilise a Trial-within-a-Cohort design involving six Enroll-HD sites across Europe and USA. This design involves longitudinal evaluation of physical fitness and activity in a cohort of people with manifest HD (n=120) and a nested randomized trial (RCT) at 3 sites (n=60) of 12-months exercise compared to usual care. The intervention incorporates a physical activity coaching program with goal setting, an associated workbook, and provision of exercise equipment and FitBit devices for self-monitoring of exercise. Assessments include fitness testing and the use of wearable technologies to capture and quantify dose (frequency, duration, intensity) of physical activity in a large HD cohort. Participants in the RCT allocated to usual activity and those from the observational cohort will provide reference data (n=90) from their annual Enroll-HD assessments that we will utilise to evaluate exercise effects in those randomized to supported exercise (n=30). Outcomes: Should the design prove to be feasible, it will pave the way for robust evaluation of exercise in HD supported by the existing Enroll cohort.